Effects of fungal beta-glucans on health – a systematic review of randomized controlled trials. Issue 8 (31st March 2021) - Vlassopoulou, Marigoula; Yannakoulia, Mary; Pletsa, Vasiliki; Zervakis, Georgios I.; Kyriacou, Adamantini
Abstract : Oral supplementation with beta-glucans demonstrates health-promoting properties, such as the prophylactic effect against the occurrence and severity of upper respiratory tract infections, primarily through the potentiation of the immune system. Abstract : Introduction : Beta-glucans are polysaccharides that exhibit a wide range of biological properties as a result of their varying chemical composition. Like all dietary fibers, they avoid catabolism in the upper gastrointestinal tract, and they reach the large intestine undigested. There, they undergo fermentation by the gut microbiota, a process that has potential beneficial effects for the host. The aim of this systematic review is to assess the effects of consumption of beta-(1 → 3, 1 → 6)-d -glucans, naturally found in the cell walls of fungi, on health outcomes. Methods : A comprehensive literature search was performed on PubMed, Cochrane Library and Web of Science to retrieve studies that applied randomized controlled trials (RCTs) to investigate the impact of exclusive oral administration of fungal beta-glucans in any form and at any dosage to healthy subjects or patients. Results : Thirty-four RCTs, of the 917 records retrieved in total, met the eligibility criteria and are included in the present review. The sources of fungal beta-glucans were Saccharomyces cerevisiae, Aureobasidium pullulans, Pleurotus ostreatus, Lentinula edodes and Ganoderma lucidum, and the dosage of supplementation ranged from 2.5 to 1000 mg daily for up to 6.5 months. The primary physiological outcome of the majority of the interventions was immunomodulation, which resulted in (a) strengthened immune defense that reduces the incidence and symptoms of cold, flu and other respiratory infections and (b) improvement of allergic symptoms. However, the findings on the induction of immune response alterations were inconsistent at the cellular and molecular levels. Another aspect is psychological wellbeing, as the cohorts that received the polysaccharides of interest reported improvement in their mood states as well as amelioration of overall wellbeing. At the same time, it might also be useful as a complementary agent to patients undergoing cancer therapies. Furthermore, supplements containing beta-(1 → 3, 1 → 6)-d -glucan administered to overweight/obese adults might have the potential to decrease comorbid conditions associated with obesity. Notably, no adverse event causally related to glucans was recorded. Conclusions : Supplementation with beta-(1 → 3, 1 → 6)-d -glucans is well-tolerated, and health-promoting properties are manifested primarily through the potentiation of the immune system. More studies are required to confirm their additional beneficial effects, to establish the optimal dose, and to reveal the underlying molecular mechanisms.